2022
DOI: 10.3389/fpls.2022.1062982
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of plant root exudates: From sample preparation to data analysis

Abstract: Plants release a set of chemical compounds, called exudates, into the rhizosphere, under normal conditions and in response to environmental stimuli and surrounding soil organisms. Plant root exudates play indispensable roles in inhibiting the growth of harmful microorganisms, while also promoting the growth of beneficial microbes and attracting symbiotic partners. Root exudates contain a complex array of primary and specialized metabolites. Some of these chemicals are only found in certain plant species for sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Future studies will benefit from evaluating whether the circadian oscillator governs root metabolite production and release at the levels of protein activity, metabolite accumulation, and metabolite transport. Assess root exudate rhythmicity across various plant developmental stages and environments : Root exudate composition changes with plant development stage (Chaparro et al., 2013) and growing substrate (McLaughlin et al., 2023), so comparative experiments using wild‐type and circadian clock mutants at different developmental stages, using various substrates, will deepen understanding of the circadian regulation of root exudation over the plant life cycle and its influence by the environment. Such investigations will benefit from non‐targeted root exudate profiling approaches to obtain a holistic assessment of circadian involvement in the release of different metabolite classes, because identification and quantification of various compound types is sensitive to the technical approach used (reviewed in Pantigoso et al., 2021; Salem et al., 2022). Assess relationships between diel or circadian exudation cycles and wider rhizosphere processes : Whilst researchers have started to analyze the effect of core circadian oscillator genes on rhizomicrobiome composition (Hubbard et al., 2018, 2021; Newman et al., 2022; Staley et al., 2017), work is needed to directly assess rhythmic metabolic interactions between root exudates and rhizosphere microbial communities (Figure 2b,c).…”
Section: Circadian Regulation Of Root Exudationmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies will benefit from evaluating whether the circadian oscillator governs root metabolite production and release at the levels of protein activity, metabolite accumulation, and metabolite transport. Assess root exudate rhythmicity across various plant developmental stages and environments : Root exudate composition changes with plant development stage (Chaparro et al., 2013) and growing substrate (McLaughlin et al., 2023), so comparative experiments using wild‐type and circadian clock mutants at different developmental stages, using various substrates, will deepen understanding of the circadian regulation of root exudation over the plant life cycle and its influence by the environment. Such investigations will benefit from non‐targeted root exudate profiling approaches to obtain a holistic assessment of circadian involvement in the release of different metabolite classes, because identification and quantification of various compound types is sensitive to the technical approach used (reviewed in Pantigoso et al., 2021; Salem et al., 2022). Assess relationships between diel or circadian exudation cycles and wider rhizosphere processes : Whilst researchers have started to analyze the effect of core circadian oscillator genes on rhizomicrobiome composition (Hubbard et al., 2018, 2021; Newman et al., 2022; Staley et al., 2017), work is needed to directly assess rhythmic metabolic interactions between root exudates and rhizosphere microbial communities (Figure 2b,c).…”
Section: Circadian Regulation Of Root Exudationmentioning
confidence: 99%
“…Assess root exudate rhythmicity across various plant developmental stages and environments : Root exudate composition changes with plant development stage (Chaparro et al., 2013 ) and growing substrate (McLaughlin et al., 2023 ), so comparative experiments using wild‐type and circadian clock mutants at different developmental stages, using various substrates, will deepen understanding of the circadian regulation of root exudation over the plant life cycle and its influence by the environment. Such investigations will benefit from non‐targeted root exudate profiling approaches to obtain a holistic assessment of circadian involvement in the release of different metabolite classes, because identification and quantification of various compound types is sensitive to the technical approach used (reviewed in Pantigoso et al., 2021 ; Salem et al., 2022 ).…”
Section: Circadian Regulation Of Root Exudationmentioning
confidence: 99%
“…In recent years, the interactions between root exudates and rhizosphere microorganisms and the associated mechanisms have attracted the attention of many researchers ( Zhao et al, 2021 ; Upadhyay et al, 2022 ). Research has shown that plants use their root exudates to regulate the nearby soil environment, shape the microbiota, and communicate with microorganisms ( Salem et al, 2022 ). Although many aspects of this process remain controversial, a wealth of evidence has indicated the ability of root exudates to regulate plant growth and development by shaping the rhizosphere microbiota ( Reinhold-Hurek et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analytical techniques such as gas chromatography coupled to mass spectrometry (GC-MS), liquid chromatography-MS (LC-MS), and/or nuclear magnetic resonance spectroscopy (NMR) are often used to characterize the metabolome of plant root exudates ( Fan et al., 2001 ; Luo et al., 2017 ; Gargallo-Garriga et al., 2018 ; Salem et al., 2022 ). Fourier-transform ion cyclotron resonance-MS (FT-ICR MS) is an ultrahigh-resolution analytical technique that has also been proven as a powerful tool for qualitative characterization of the metabolome of complex plant extracts ( Maia et al., 2021 ) and for characterizing the root exudate composition of different plant species ( Miao et al., 2020 ; Lohse et al., 2022 ; Ulrich et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the choice of analytical technology depends on multiple factors, such as high throughput capacity, optimal metabolome coverage, and other factors, FT-ICR MS yields high mass accuracy and resolution power, with a mass-to-charge ratio (m/z) range of 200 to 900 ( Hsu et al., 2011 ; Park et al., 2013 ), which offers valuable insight into elemental and compound diversity of plant secondary metabolites ( Takahashi et al., 2008 ; Maia et al., 2021 ). Further, by mapping the molecular formula to databases reveal potential functional pathways and direct the discovery of novel compounds as inherent advantages that are not as achievable with traditional approaches ( Salem et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%